Generics and Alternatives - Kochari, Arnold; Van Rooij, Robert; Schulz, Katrin (Frontiers in Psychology, 2020)
In this paper we argue that for the (probabilistic) interpretation of generic sentences of the form `Gs are f', three types of alternatives play a role: (i) alternative subgroups of G, (ii) alternative features of f, and (iii) alternative groups, or kinds, of G. In the first part of this paper we argue for the relevance of these alternatives. In the second part, we describe the results of some experiments that empirically tested in particular the last use of alternatives.